2004
DOI: 10.1007/s00296-003-0373-5
|View full text |Cite
|
Sign up to set email alerts
|

Articular, B-cell, non-Hodgkin?s lymphoma mimicking rheumatoid arthritis: synovial involvement in a small hand joint

Abstract: Polyarticular joint manifestations as the predominant symptom of non-Hodgkin's lymphoma (NHL) are quite rare. In the absence of peripheral lymph node and visceral involvement, lymphomas presenting as polyarthritis create a problem for the patients as another rheumatic disease. We present a case that had been diagnosed with rheumatoid arthritis because of symmetrical articular symptoms. The patient later developed severe pain and marked swelling in her right fourth finger, and a diagnosis of septic arthritis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Autoimmune paraneoplastic disorders have been described in lymphoma 6 . We speculate that polyarthralgia may result from host response to tumor antigens and cytokine‐driven synovial inflammation 7 . Reed–Sternberg cells could secrete a variety of inflammatory cytokines and chemokines, of which interleukin (IL)‐1, IL‐6, and tumor necrosis factor α (TNF‐α) are particularly associated with arthritis, explaining the initial clinical manifestation mimicked rheumatic disease 6 …”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune paraneoplastic disorders have been described in lymphoma 6 . We speculate that polyarthralgia may result from host response to tumor antigens and cytokine‐driven synovial inflammation 7 . Reed–Sternberg cells could secrete a variety of inflammatory cytokines and chemokines, of which interleukin (IL)‐1, IL‐6, and tumor necrosis factor α (TNF‐α) are particularly associated with arthritis, explaining the initial clinical manifestation mimicked rheumatic disease 6 …”
Section: Discussionmentioning
confidence: 99%
“…Primary synovium lymphoma without bone involvement is extremely rare. On the review of the English-language literature from 1980 to present, we found 14 cases of primary synovial B-cell NHL [1, 6-18] (Table 1). The reported literature showed various joint involvement such as knee (most common), elbow and small joints of hand and feet.…”
Section: Discussionmentioning
confidence: 99%
“…The knee joint (11 cases) is the most commonly involved joint followed by the elbow (two cases), sternoclavicular joint (one case), shoulder (one case) and wrist (one case) ( 1 ). Joint involvement in NHL usually presents with symptoms suggestive of an inflammatory arthropathy or low grade infection such as joint pain, swelling and limitation of movement affecting a single joint rather than multiple joints ( 2 , 5 , 6 ). A minority of patients also has systemic symptoms such as weight loss, night sweats and fever ( 2 , 7 ).…”
Section: Discussionmentioning
confidence: 99%